A thermostable and CBM2-linked GH10 xylanase from Thermobifida fusca for paper bleaching - Wu, Xiuyun; Shi, Zelu; Tian, Wenya; Liu, Mengyu; Huang, Shuxia; Liu, Xinli; Yin, Hua; Wang, Lushan (Frontiers in Bioengineering and Biotechnology, 2022)
Xylanases have the potential to be used as bio-deinking and bio-bleaching materials and their application will decrease the consumption of the chlorine-based chemicals currently used for this purpose. However, xylanases with specific properties could act effectively, such as having significant thermostability and alkali resistance, etc. In this study, we found that TfXyl10A, a xylanase from Thermobifida fusca, was greatly induced to transcript by microcrystalline cellulose (MCC) substrate. Biochemical characterization showed that TfXyl10A is optimally effective at temperature of 80 °C and pH of 9.0. After removing the carbohydrate-binding module (CBM) and linker regions, the optimum temperature of TfXyl10A-CD was reduced by 10 °C (to 70 °C), at which the enzyme’s temperature tolerance was also weakened. While truncating only the CBM domain (TfXyl10AdC) had no significant effect on its thermostability. Importantly, polysaccharide-binding experiment showed that the auxiliary domain CBM2 could specifically bind to cellulose substrates, which endowed xylanase TfXyl10A with the ability to degrade xylan surrounding cellulose. These results indicated that TfXyl10A might be an excellent candidate in bio-bleaching processes of paper industry. In addition, the features of active-site architecture of TfXyl10A in GH10 family were further analyzed. By mutating each residue at the -2 and -1 subsites to alanine, the binding force and enzyme activity of mutants were observably decreased. Interestingly, the mutant E51A, locating at the distal -3 subsite, exhibited 90% increase in relative activity compared with wild-type (WT) enzyme TfXyl10A-CD (the catalytic domain of TfXyl110A). This study explored the function of a GH10 xylanase containing a CBM2 domain and the contribution of amino acids in active-site architecture to catalytic activity. The results obtained provide guidance for the rational design of xylanases for industrial applications under high heat and alkali-based operating conditions, such as paper bleaching.